Programmed shape of glassy nematic sheets with varying in-plane director fields: A kinetics approach. (January 2018) - He, L.H.; Zheng, Y.; Ni, Y.
Abstract: Programmed deformation of glassy nematic sheets with continuously varying in-plane director fields is studied using Föppl-von Kármán plate theory. To solve the nonlinear governing equations, an efficient kinetics approach is developed, in which the deformed shape of a sheet can be recovered from the steady-state solution of an overdamped evolution system driven by elastic energy release. Numerical examples are given for circular nematic sheets with two kinds of director alignment. It is found that the director pattern, the radius-to-thickness ratio, and the elastic anisotropy along and normal to the director all can strongly influence the buckling morphologies. These results are important to the exploration of encoding three-dimensional shapes using glassy nematic sheets.